The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11051-022-05534-z
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cosmeceutical nanotechnology for hyperpigmentation treatment

Abstract: Hyperpigmentation is a common and major skin problem that affects people of all skin types. Despite the availability of various depigmentation active ingredients for skin hyperpigmentation disorder, none of them are completely satisfactory due to their poor permeability through the skin layer and significant toxicity, thereby causing severe side effects such as irritative dermatitis, erythema, itching, and skin flaking. Nanotechnology plays an important role in advancing the cosmeceutical formulation by improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…By 2025, it is expected that the market for these skin care products will reach an estimated USD 716 billion [ 7 ]. Maintaining good care of the skin also ensures remarkable esthetic attributes in modern society [ 8 ]. Plant extracts, through their antioxidant effects, can protect the skin from exogenous and endogenous factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…By 2025, it is expected that the market for these skin care products will reach an estimated USD 716 billion [ 7 ]. Maintaining good care of the skin also ensures remarkable esthetic attributes in modern society [ 8 ]. Plant extracts, through their antioxidant effects, can protect the skin from exogenous and endogenous factors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous studies, azelaic acid-loaded NLCs was resulted in more occlusive properties, enhanced skin permeation, targeted drug delivery to the melanocytes with enhanced clinical efficacy ( Kumari et al, 2015 ). Moreover, the sustained release capability of azelaic acid-loaded NLCs would be advantageous for topical drug delivery due to the prolonged localized drug deposition within the skin layers ( Tangau et al, 2022 ).…”
Section: New Approaches In Melasma Pharmacotherapymentioning
confidence: 99%
“…Nanotechnology plays a vital part in the cosmeceutical industry by enhancing the stability, permeability, solubility, safety, and loading capacity of active pharmaceutical ingredients. [74] Hiranphinyophat and his colleagues described a PIPP (poly(2isopropoxy-2-oxo-1,3,2 dioxaphospholane) modified NCs of cellulose for delivery of drugs that are insoluble in water. From the results, it was observed that surface-modified NCs can improve the solubility, efficiency of emulsification, and penetration of drugs in deep skin layers.…”
Section: Hyperpigmentationmentioning
confidence: 99%
“…Nanotechnology plays a vital part in the cosmeceutical industry by enhancing the stability, permeability, solubility, safety, and loading capacity of active pharmaceutical ingredients. [ 74 ]…”
Section: Therapeutic Application Of Nanocrystal In Dermatological Com...mentioning
confidence: 99%